1974
DOI: 10.1126/science.185.4150.537
|View full text |Cite
|
Sign up to set email alerts
|

Cerebral Dominance in Musicians and Nonmusicians

Abstract: Musically experienced listeners recognize simple melodies better in the right ear than the left, while the reverse is true for naive listeners. Hence, contrary to previous reports, music perception supports the hypothesis that the left hemisphere is dominant for analytic processing and the right hemisphere for holistic processing.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

14
113
4
5

Year Published

1980
1980
2005
2005

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 679 publications
(136 citation statements)
references
References 26 publications
14
113
4
5
Order By: Relevance
“…Peretz and colleagues (Peretz & Babai, 1992;Perez & Morais, 1988) observed a left-ear advantage for contour information and a rightear advantage for interval information in musicians and nonmusicians, but an earlier study reported a right-ear advantage in musicians and a left-ear advantage in nonmusicians in a musical pattern identification task (Bever & Chiarello, 1974). This difference between adult musicians and nonmusicians reflects the possibility that experience or listening strategy influences asymmetries in musical processing.…”
Section: Discussionmentioning
confidence: 85%
“…Peretz and colleagues (Peretz & Babai, 1992;Perez & Morais, 1988) observed a left-ear advantage for contour information and a rightear advantage for interval information in musicians and nonmusicians, but an earlier study reported a right-ear advantage in musicians and a left-ear advantage in nonmusicians in a musical pattern identification task (Bever & Chiarello, 1974). This difference between adult musicians and nonmusicians reflects the possibility that experience or listening strategy influences asymmetries in musical processing.…”
Section: Discussionmentioning
confidence: 85%
“…On the other hand, descriptions of the strategies that participants are believed to be using when attending to interval-versus contourchange often evoke a temporal mechanism: attending to intervals within a melody may involve a more fine-grained temporal analysis than attending to contour, which may be accomplished by one, wide temporal window. It is noteworthy in this regard that Bever and Chiarello (1974) study demonstrated the right-ear, "local" bias in their musicians for the old and new melody recognition just after they had been asked to identify whether a specific two-tone sequence had been present in the same melody. Further, Peretz (1987) reported that when conditions encourage a self-terminating, analytic search, "different" responses are made before the melodies are complete, based on the first noticeable change, with a right-ear advantage.…”
Section: Previous Approaches To Auditory Local-global Structurementioning
confidence: 92%
“…Previous approaches to auditory local-global processing have largely been pursued within the music cognition literature, and largely stem from a study by Bever and Chiarello (1974) in which musically trained participants demonstrated better discrimination between old and new melodies when presented to the right ear, whereas the musically naïve were better when the melodies were presented to the left ear. The authors suggested that the musicians adopted a more "analytic" strategy, which resulted in an advantage for the left hemisphere and right ear.…”
Section: Previous Approaches To Auditory Local-global Structurementioning
confidence: 99%
“…Devido à grande variabilidade de aptidões musicais nos seres humanos, o estudo do reconhecimento melódico e sua reprodução deve ser conduzido através de testes simples, pois os mais complexos deverão ser apresentados apenas para indivíduos que desenvolveram habilidades musicais, por apresentarem diferentes estratégias no processamento desses aspectos 4,13,[27][28][29] . O nosso teste consistiu de uma frase melódico-verbal desconhecida, a qual permitiu que os indivíduos não músicos fossem capazes de entoá-la, como aconteceu com o Grupo Controle.…”
Section: B) Reconhecimento E Reprodução Melódico-verbalunclassified
“…Dentre os poucos trabalhos que estudam o envolvimento das epilepsias e os aspectos musicais, destacam-se os que têm possibilitado o estabelecimento de hipóteses quanto às atribuições dos hemisférios cerebrais em relação a esses aspectos. Assim, nos indivíduos destros atribui-se ao hemisfério esquerdo o julgamento envolvido na percepção do ritmo musical, nos aspectos sequenciais e analíticos da música, duração do som e ordem temporal e ao hemisfério direito, o julgamento na percepção da altura do som, harmonia, timbre, intensidade, melodias e canto [10][11][12][13] . No entanto, o desempenho dos músicos, para alguns desses aspectos musicais, não ocorre exatamente da mesma forma pois, por terem passado por um processo de aprendizagem e treinamento musical, podem ter desenvolvido habilidades musicais nos dois hemisférios [13][14][15] .…”
unclassified